Bevacizumab in the pre-operative treatment of locally advanced rectal cancer: A systematic review - Fornaro, Lorenzo (Baishideng Publishing Group Inc, 2014)
Despite advances in the management of patients with locally advanced, non-metastatic rectal adenocarcinoma (LARC), prognosis remains largely unsatisfactory due to a high rate of distant relapse. In fact, currently available neoadjuvant protocols, represented by fluoropyrimidine-based chemo-radiotherapy (CT-RT) or short-course RT, together with improved surgical techniques, have largely reduced the risk of local relapse, with limited impact on distant recurrence. Available results of phase III trials with additional cytotoxic agents combined with standard CT-RT are disappointing, as no significant reduction in the risk of recurrence has been demonstrated. In order to improve the control of micrometastatic disease, integrating targeted agents into neoadjuvant treatment protocols thus offers a rational approach. In particular, the antiangiogenic agent bevacizumab has demonstrated synergistic activity with both CT and RT in pre-clinical and clinical models, and thus may represent a suitable companion in the neoadjuvant treatment of LARC. Preliminary results of phase I-II clinical studies are promising and suggest potential clinical parameters and molecular predictive biomarkers useful for patient selection: treatment personalization is indeed the key in order to maximize the benefit while reducing the risk of more complex neoadjuvant treatment schedules.